(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research outlines the creation of a tri-band radio-frequency (RF) detection and monitoring system aimed at addressing the increasing abuse of mobile phones and other wireless electronic gadgets in classrooms and exam venues. The system employs a passive detection method to ensure compliance with regulatory standards while safeguarding vital communication services, especially during emergencies. The system constantly monitors the surroundings to identify RF signals from devices functioning within the cellular, Wi-Fi, and Bluetooth frequencies. Detected signals are analyzed using parameters such as Received Signal Strength Indicator (RSSI), spectral occupancy, and temporal features to enable precise categorization of wireless activity. The hardware setup includes a microcontroller system, NRF24 transceiver modules for detecting 2.4 GHz Wi-Fi and Bluetooth, and a 1N34A germanium diode-based RF detector for sensing cellular signals in the 900 MHz to 2.4 GHz spectrum. A TFT display interface, along with an alert system, enables real-time tracking and alerts. The system is developed to encompass standard classroom and exam hall settings (150 m² to 450 m²) and accommodates adjustable sensitivity and time-controlled functionality. Experimental findings showed that Wi-Fi signals display consistent behavior, Bluetooth signals manifest as sporadic spikes, and cellular signals present as burst transmissions, facilitating dependable classification. The proposed solution provides an affordable, flexible, and unobtrusive system for improving academic honesty and minimizing wireless examination misconduct.